Reconfiguration of an industrial steam generator using bond graph modelling. (23rd July 2007) - Samantaray, A.K.; Ghoshal, S.K.; Medjaher, K.; Bouamama, B. Ould
In this paper, we survey some recent advances made in the field of Bond Graph (BG) modelling and show that it is well suited to solve modelling, fault diagnosis and Fault Tolerant Control (FTC) problems in complex processes. We consider the reconfiguration scheme for a steam generator process, which is a safety-critical complex thermo-fluid process involving storage and transport of under saturated and saturated fluids, as well as phase transformations. BG modelling, which is a unified tool for multienergy domain system representation, is not only used to model the process but also to generate the fault indicators and to determine various redundancies. These redundancies are then used to determine possible system reconfigurations and Operating Modes (OMs), by taking various operating constraints (equipment availability, saturations, power ratings, etc.) into consideration. The developed algorithms are implemented to supervise the steam generator process and the experimental results are presented.